Analysing the Occupational Health and Safety Knowledge of Science Teachers - Karakoyun, Gülen Önal; Sarul, Meysa Simge; Asiltürk, Erol; Polat, Mehmet (My University, 2025)
This study was conducted to evaluate the occupational health and safety knowledge of science teachers in Malatya, Turkey. ‘Occupational Health and Safety’ questionnaire was used as a data collection tool in the descriptive survey method. The results of the survey conducted with a total of 352 teachers were analysed by SPSS analysis and it was found that teachers had a high level of knowledge in this field and were aware of the rules and occupational risks. In addition, it was determined that teachers received basic occupational health and safety and first aid trainings more than fire safety and hygiene trainings and could intervene appropriately in emergencies. There is also a widespread opinion that occupational health and safety course should be compulsory in the curriculum. Teachers stated that they frequently encountered back, neck and joint disorders and infections.
Keywords: Teacher; student; science; Occupational health and safety; school